Use of a New Ocular Insert versus Conventional Mydriasis in Cataract Surgery. (30th May 2013) - Torrón, C.; Calvo, P.; Ruiz-Moreno, O.; Leciñena, J.; Pérez-Iñigo, A.
Abstract : Background . To compare the efficacy and safety of a new ocular insert versus conventional mydriasis in cataract surgery. Methods . We selected 70 patients undergoing cataract surgery. Thirty five patients (Group 1) received instillation of mydriatic drops (tropicamide 1%, phenylephrine 10%, and cyclopentolate 1%) prior to surgery, and 35 patients (Group 2) had a Mydriasert insert (Théa Pharma) (0.28 mg of tropicamide and 5.4 mg of phenylephrine hydrochloride) placed in the inferior fornix. Pupil size before and after surgery, blood pressure, and heart rate were measured. Results . Before surgery, pupil diameter was 9.44 ± 1.17  mm in Group 1 and 9.05 ± 1.54 in Group 2 (P > 0.05 ). Twenty four hours after surgery, pupil diameter was 5.20 ± 1.54  mm in Group 1 and 3.33 ± 1.15 in Group 2 (P < 0.001 ). There were no statistically significant differences in blood pressure or heart rate between groups. Conclusions . The effect of the Mydriasert insert was similar to conventional mydriatic agents. Pupil size was restored to normal faster when using the Mydriasert insert compared with conventional mydriatic agents for pupil dilation.